1950: What the scientists are saying. (1st November 2020) - Einstein, Albert; Teller, Edward
ABSTRACT: These companion articles were originally published in the March 1950 issue of the Bulletin, in the wake of President Harry Truman's announcement that the United States would pursue a hydrogen bomb. They are republished here as part of our special issue commemorating the 75 th year of the Bulletin.